PENGARUH MOTIVASI, DISIPLIN, FASILITAS KERJA DAN KEBIJAKAN PIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN BELAWAN - Mora Gandi Ritonga (Universitas Islam Islam Sumatera Utara, 2020)
Based on the analysis results obtained There is a significant effect between the value of -t Motivation = 4.357, while t-table with dk 86 (attached) of 1.66, then t arithmetic t-table thus partially there is a significant influence between motivation on performance, Value of t Discipline = 4,574, while t-table with dk 86 (attached) of 1.66, then t arithmetic ˃ t table thus partially there is a significant influence between discipline on performance. Value of work facility t = 1.935 while t-table with dk 86 (attached) is 1.66, then t count t table, thus partially there is a significant influence between work facilities on performance. The value of t policy leadership = 1,780 while the t-table with dk 86 (attached) of 1.66, then t arithmetic t table thus partially there is a significant influence between leadership policies on performance. The F-count value is 60.162 while the F-table value (attached) with the numerator dk 4 and the denominator dk 81 is 2.48 where F-count F table (60.162 2.48) it can be mentioned that together ( multiple) there is a positive and significant influence of motivation, discipline, work facilities and leadership policies on performance.